An individually randomised controlled multi-centre pragmatic trial with embedded economic and process evaluations of early vocational rehabilitation compared with usual care for stroke survivors: study protocol for the RETurn to work After stroKE (RETAKE) trial - Radford, Kathryn A.; Craven, Kristelle; McLellan, Vicki; Sach, Tracey H.; Brindle, Richard; Holloway, Ivana; Hartley, Suzanne; Bowen, Audrey; O’Connor, Rory; Stevens, Judith; Philips, Julie; Walker, Marion; et al. (Current controlled trials in cardiovascular medicine, 2020)
Background Return to work (RTW) is achieved by less than 50% of stroke survivors. The rising incidence of stroke among younger people, the UK economic forecast, and clinical drivers highlight the need for stroke survivors to receive support with RTW. However, evidence for this type of support is lacking. This randomised controlled trial (RCT) will investigate whether Early Stroke Specialist Vocational Rehabilitation (ESSVR) plus usual care (UC) (i.e. usual NHS rehabilitation) is more clinically and cost-effective for supporting post-stroke RTW, than UC alone. Methods Seven hundred sixty stroke survivors and their carers will be recruited from approximately 20 NHS stroke services. A 5:4 allocation ratio will be employed to randomise participants to receive ESSVR plus UC, or UC alone. The individually tailored ESSVR intervention will commence within 12 weeks of stroke onset and be delivered for up to 12 months as necessary by trained RETAKE occupational therapists in the community, participants’ homes or workplaces, and outpatient/inpatient therapy settings, via telephone, email, or SMS text message. Outcome data will be collected via self-report questionnaires administered by post or online at 3, 6, and 12 months follow-up. The primary outcome will be self-reported RTW and job retention at 12 months (minimum 2 h/week). Secondary outcomes will include mood, function, participation, health-related quality of life, confidence, intervention compliance, health and social care resource use, and mortality. An embedded economic evaluation will estimate cost-effectiveness and cost-utility analyses from National Health Service (NHS) and Personal Social Services (PSS) perspectives. An embedded process evaluation will employ a mixed methods approach to explore ESSVR implementation, contextual factors linked to outcome variation, and factors affecting NHS roll-out. Discussion This article describes the protocol for a multi-centre RCT evaluating the clinical- and cost-effectiveness of an early vocational rehabilitation intervention aimed at supporting adults to return to work following a stroke. Evidence favouring the ESSVR intervention would support its roll-out in NHS settings. Trial registration ISRCTN, ISRCTN12464275 . Registered on 26 February 2018.